KERAGAMAN LUMUT KERAK PADA TANAMAN TEH (Camellia sinensis (L.) Kuntze) DI PERKEBUNAN TEH PT. SARANA MANDIRI MUKTI KABUPATEN KEPAHIANG PROVINSI BENGKULU - Rochmah Supriati; Helmiyetti Helmiyetti; Dwi Agustian (Research Center for Biology-Indonesian Institute of Sciences, 2021)
Lichen is a mutualism symbiotic organism between fungi (mycobiont) and photosynthetic symbiont in the form of algae (photobiont). It can be found from the lowlands to the highlands, growing epiphytically on soil, rocks, weathered wood, and tree bark, as shown on surface of the tea plants (Camellia sinensis (L.) Kuntze) in The PT Sarana Mandiri Mukti Tea plantation in Kepahiang regency, Bengkulu Province. The purpose of this research was to identify and find out the species of epiphytic lichens on the tea plant in this place. The study was conducted in May–November 2019. Samples was collected purposively, by taken ephyphitic lichens growth on the bark of tea plants stems. Then, samples was identified based on morphological characteristics at the Basic Science Biosystematics Laboratory, FMIPA University of Bengkulu. The data obtained were analyzed descriptively. It was identified as many as 35 species of lichens from the Ascomycota division, belonged to three classes, six orders, 11 families; those are Graphidaaceae, Stereocaulaceae, Parmeliaceae, Lecanoraceae, Malmideaeceae, Pertusariaceae, Teloschistaceae, Caliciaceae, Physciaceae, Arthoniaceae, dan Pyrenulaceae. 23 species have crustose type thalus and 12 species have foliose type thalus.